1978
DOI: 10.1007/bf00975675
|View full text |Cite
|
Sign up to set email alerts
|

A gamma camera method for quantitation of split renal function in children followed for vesicoureteric reflux

Abstract: A method for quantitative estimation of split renal function using a computerized gamma camera system is described. 42 children and adolescents with existing or preexisting vesicoureteric reflux and recurrent urinary tract infection were investigated. Total renal clearance of DTPA was calculated with a disappearance curve derived from the largest extrarenal area in the field of view of a gamma camera with diverging collimator. Split renal function was estimated with the slopes of second phase renograms. The pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…It has previously been shown that there is a significant correlation between renal parenchymal area determined from urography and GFR in the same renal disorder (1,7,16). The results were confirmed in the present investigation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has previously been shown that there is a significant correlation between renal parenchymal area determined from urography and GFR in the same renal disorder (1,7,16). The results were confirmed in the present investigation.…”
Section: Discussionsupporting
confidence: 91%
“…During the last few years length (12,14) and renal volume (2,6,14) have been determined by ultrasonography. Renal parenchymal area measured on the urogram has been shown to be directly related to glomerular filtration rate (1,7,16) in some childhood renal disorders.…”
mentioning
confidence: 99%
“…They studied the inulin clearanee of each kidney by catheterizing the bladder and obtaining urine separately from each kidney by external compression of the contralateral ureter. Tamminen et al (17) also found a correlation bctween kidney parenchymal area and renal function in patients with recurrent urinary tract infection with reflux, using 99mTc-DTPA-clearanee as a crite-Vihma etat non of renal function. A good correlation between kidney parenchymal area and kidney function was demonstrated in patients with hydronephrosis, recurrent pyelonephritis or sin-,le kidney by Haugstvedt et al (5), who used a combination of 25I-Hippuran renography and 51 Cr-EDTA-clearance for calculation ofindividual kidney function.…”
Section: Discussionmentioning
confidence: 90%
“…An exact description ofthe method has been given by Tamminen et al (17). The patients were in anormal state of hydration.…”
Section: Radioisotope Methodsmentioning
confidence: 99%
“…The split isotope uptake was estimated from the ratio of the slopes of the linear uptake phase of the renogram. The washout pattern was given routinely but not the half time [10,11]. Mercaptoacetyl triglycine (MAG-3) was used as an alternative in the initial examinations in 3 patients.…”
Section: Methodsmentioning
confidence: 99%